Some Aspects of the Evidentiary Process during the Arbitration of Civil Cases - L. V. Sapeiko (Bulletin of Kharkiv National University of Internal Affairs)
The institution of proving and evidence in civil cases considered by arbitration courts has been studied. According to the author, the most significant problem that hinders the full functioning of arbitration courts and the transfer of disputes for their resolution is the presence of certain legislative gaps, as well as insufficient regulation of arbitration, in particular in the field of evidentiary activity. The purpose of the article is to determine the system of evidence in civil cases considered within the arbitration procedure, as well as the competence of arbitration courts in the field of evidentiary activity. The comparative and legal analysis of normative provisions of the Law of Ukraine “On Arbitration Courts” and the civil procedural legislation of Ukraine related to evidence and their research has been carried out. The author has for the first time studied the main problems of proving and evidence in civil cases, submitted for consideration and solution to the arbitration court by the agreement between the parties to the dispute, and has provided propositions to improve the Law of Ukraine “On Arbitration Courts” to overcome these problems. The author has substantiated the conclusion on the need to introduce a separate norm in the Law of Ukraine “On Arbitration Courts”, which should clearly define the means of proving, which are the basis for establishing the circumstances of the case during the arbitration proceedings. These should include written, physical and electronic evidence, expert opinions and explanations of parties, third parties and their representatives. It has been emphasized that the testimony of witnesses, considering the specifics of obtaining and ensuring the reliability of such a source of evidence, which may be implemented only by the state court, can not be attributed to means of evidence in arbitration. If the parties plan to use the testimony of a witness as evidence, they can refer their dispute to the state court. The results obtained during the study can be used in the process of reforming the current legislation of Ukraine regulating the activities of arbitration courts.